Methodology of Da'wah to The Non-Muslim Chinese in Malaysia: A Preliminary Observation - Osman Abdullah @ Chuah Hock Leng (Universiti Sains Islam Malaysia, 2024)
Methodology of Da'wah especially to non-Muslims is very vital for the preachers to observe the proper norms in the Islamic perspective nowadays. In the context of preaching to non-Muslim Chinese in Malaysia, the preachers must understand their backgrounds and their perceptions towards Islam before preaching. This article highlights the non- Muslim Chinese negative perceptions towards Islam and its ummah and suggest means and approaches of preaching with hikmah to bring Islam to the non-Muslim Chinese in Malaysia.